2000
DOI: 10.3109/09513590009167698
|View full text |Cite
|
Sign up to set email alerts
|

The use of a starting dose of recombinant follicle stimulating hormone for controlled ovarian hyperstimulation: a randomized pilot study

Abstract: The aim of this study was to compare the costs and effects of two different controlled ovarian hyperstimulation treatments: a starting dose of recombinant follicle stimulating hormone (FSH) followed by highly purified urinary FSH; or highly purified urinary FSH alone. Forty-six infertile patients, after being given luteal gonadotropin-releasing hormone (GnRH) agonist, were randomly assigned to the two stimulation protocols. During the ovarian stimulation regimen the patients underwent transvaginal ultrasonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…To our knowledge, this is the first time to describe the findings of proportion of large, medium, and small follicles in human stimulated ovaries. It is generally believed that larger follicles may result in higher oocyte recovery rates (10,11) and may yield more mature oocytes (12). In bovine, it was shown that oocytes derived from smaller follicles had increased fertilization abnormalities as a result of incomplete synthesis of maternal RNA transcripts (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first time to describe the findings of proportion of large, medium, and small follicles in human stimulated ovaries. It is generally believed that larger follicles may result in higher oocyte recovery rates (10,11) and may yield more mature oocytes (12). In bovine, it was shown that oocytes derived from smaller follicles had increased fertilization abnormalities as a result of incomplete synthesis of maternal RNA transcripts (13,14).…”
Section: Discussionmentioning
confidence: 99%